Multi-purpose high-resolution nanoscale table-top ptychography at 13.5 nm - Liu, C.; Eschen, W.; Loetgering, L.; Schuster, V.; Klas, R.; Kirsche, A.; Berthold, L.; Iliou, A.; Steinert, M.; Pertsch, Thomas; Hillmann, F.; Krause, M.; et al. (Optics InfoBase Conference Papers, 2022)
We present our latest results on table-top ptychographic imaging at 13.5 nm. An overview and the identification of interesting areas are achieved with infrared illumination. XUV illumination provides sub-20-nm-resolution amplitude- and phase images.
CRIS-Team Scopus Importer:2023-04-20